FAMILY SUPPORT IN PATIENTS OF TYPE 2 DIABETES MELLITUS BANGETAYU HEALTH CENTER IN SEMARANG, RASCH MODEL ANALYSIS - Iskim Luthfa (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2016)
Diabetes mellitus is a chronic disease that will be suffered lifetime. Patients with type 2 DM are encouraged to do self-care regularly to prevent severe complications. Self-care which is performedÂ routinely would induce a feeling of bored and tired, thereby causing type 2 diabetes patients become undisciplined doing self-care. Family support helps people with type 2 diabetes to stay disciplined perform self-care. But not all families are able to provide effective support. This research is descriptive analytic, with total sample of 56 respondents. Analysis of data used Rasch Model (Rasch Measurement Model). Instrument to determine family support used Hensarling Diabetes Family Support Scale (HDFSS). The results of this study indicated that family support to word patients with type 2 diabetes were mostly low (67.9%), the easiest form of support given was related to emotional support (-4,05) and the most difficult support was support related information (1.71). The results of this study contributes to word diabetes disease management needs family support (family support), thus it is necessary to develop intervention strategies to improve family support.Keywords: Family Support, Diabetes Mellitus Type 2, Rasch MODEL.